THE ROLE OF PURCHASE INTENTION IN MEDIATING HALAL PRODUCT LITERACY, HALAL LABEL KNOWLEDGE, AND CONSUMER ATTITUDES TOWARDS GENNERASI Z PURCHASING DECISIONS AT STREET VENDORS IN PEKALONGAN. - Muftikhatul Aeni; Panca Kurniati; Nur Kholidah (Universitas PGRI Semarang, 2025)
This study examines the effect of halal product literacy, halal label knowledge, and consumer attitudes on Generation Z food purchasing decisions in Pekalongan City, with purchase intention as a mediating variable. Using a quantitative approach and probability sampling with simple random sampling method, 186 respondents were obtained. Data were collected through an online survey (Google Form) and analyzed with SEM. The results show that halal literacy, consumer attitudes, and purchase intention have a significant effect on purchasing decisions, while halal labeling does not. Purchase intention mediates the effect of halal literacy and consumer attitudes, but not the halal label. This study highlights the importance of halal literacy and understanding